Digital infrastructures of climate disinformation research: A scoping review across online platforms - Tucci, Giulia; Carneiro, Bia; Ruscica, Giosue (2025)
A scoping review of how researchers use digital tools, data extraction, and computational methods to study climate change dis/misinformation on social media and other online platforms.